BUDAYA KONTEMPLASI SUATU KUNCI KEBAHAGIAAN HIDUP (WELL BEING): Dalam Perspektif Psikologi Islami - Sutarjo Sutarjo (Universitas Ahmad Dahlan, 2013)
Contemplation becomes a necessity for individuals who want his happiness. Happiness is here not only means happiness lahiriyah alone, but also about the inner happiness that is hard to measure empirically.In this paper the word contemplation more mentioned the term